(untitled) (Media Kesehatan Masyarakat Indonesia, 2022)
COVID-19 exhibits a wide variety of symptoms, ranging from mild, moderate, severe, and critical respiratory dysfunctions up to death. Therefore, this study aimed to examine the demographic, clinical, and laboratory profile of COVID-19 patients admitted to Udayana University Hospital, Bali, during the first three months of the pandemic. Data were collected from the electronic medical records of 236 patients hospitalized from April to June 2020. The samples had a mean age of 40 years old, and they consisted of 58.50% male. Based on the records, the common clinical characteristics included fever (52.5%) and cough (47.5%), followed by less common traits, such as sore throat (18.2%), dyspnea (10.2%), flu (8.9%), and headache (3.8%). Laboratory results during admission showed an average lymphocyte count of 2.16 ± 2.19 × 109 cells/L and a neutrophil- lymphocyte ratio of 3.02 ± 3.41. The majority of patients were private corporation employees (30.51%), followed by migrant workers (21.19%). Furthermore, a fatality rate of 1.69% was recorded in the study hospital. These results were expected to provide epidemiological knowledge of COVID-19 patients, which can help clinicians to anticipate possible outcomes during treatment.